Efficient lot batching system for furnace operation - Ibrahim, Kader; Chik, Mohd Azizi; Nizam, Wan Shamsir; Nyioh, Li Fem; Za'bah, Nor Farahidah (2003)
At a semiconductor foundry where a wide range of products are manufactured using the make-to-order model, it is important to optimize the lot batching in diffusion area since the loading size in most machines are in quantities of 100 to 150 wafers. This paper describes a real time dispatching system that has been developed to reduce lot queue time in the furnace operations. Emphasis on-customer delivery date, bottleneck tool and batching behavior was given in rule building for the overall systems implementation in diffusion furnace operation. The main component of this project is the rule built considering queue time restriction between pre-clean and furnace operation, allowable waiting time to maximize the batch, queue time consideration to next process such as polysilicon deposition, furnaces due for scheduled maintenance, bottleneck tool idling, process cycle time versus lot priority considerations and etc. With the implementation of this system we are able to reduce manufacturing cost, increase tool utilization, reduce overall cycle-time and meet customer delivery dates. This implementation has resulted in much better material movement and has also made the manufacturing line more linear.